Bounded rational expectations and the stability of interest rate policy - Gomes, O.; Mendes, D. A.; Mendes, V. (Physica A, 2008)
The New Keynesian model has recently been subject to two serious criticisms: the model cannot produce plausible inflation and output dynamics following a monetary shock, and the stability of its dynamics suffers from indeterminacy. The procedures that have been proposed to eliminate these two shortcomings fall into two categories: the introduction of some sort of backward price indexation into the standard model and/or other forms of stickiness (like sticky information); and the adoption of some form of policy rule that completely offsets the effects of forward looking dynamics in the optimization process. In this paper we do not eradicate forward looking behavior from the dynamics of the New Keynesian model, neither do we impose some form of backward price indexation. We assume that private economic agents have forward looking behavior and that they do try to optimize with all available information; the only novelty is that they are allowed to make small mistakes near the rational expectations equilibrium, in a fully deterministic setup. These “near rational” or “bounded rational” expectations show that the dynamics of the model with active interest rate rules is much richer than the simple problem of local indeterminacy as is usually found in the literature.